Learning Guidance As An Effort To Overcome Learning Difficulties Of Students In Ngawensari Village - Alfina Kusumadewi; Muhammad Aqil Luthfan (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
Various efforts have been made by the government to improve the quality of education in Indonesia both in terms of quality and quantity. This effort is carried out starting from elementary education to tertiary education. Law No. 20 of 2003 on the National Education System states that "The purpose of education is to educate the nation, form reliable and competitive human resources, form character and social spirit, be cultured, have noble morals and character, and have broad insight and mastery of science and technology". From several cases encountered, many students still experience learning difficulties in several subjects in class which causes them to be unable to master the material given. Therefore, tutoring services are provided so that students are motivated to create student interest in school lessons and so that students can get out of the problem of learning difficulties. The method used in this writing is a qualitative descriptive method, the author wants to express as clearly as possible about the influence of tutoring on efforts to overcome student learning difficulties.